Disease-Associated Anemia: An Integrated Review of Pathophysiology, Diagnosis, and Therapeutic Implications (Journal of Tropical Pharmacy and Chemistry, 2025)
Disease-associated anemia is a heterogeneous and prevalent clinical problem, arising from diverse underlying conditions that interfere with erythropoiesis, red blood cell survival, iron metabolism, or blood loss. Major underlying causes include chronic kidney disease, chronic inflammation or infection, malignancy, bone marrow failure syndromes, haemoglobinopathies, autoimmune haemolysis, and chronic blood loss (e.g., gastrointestinal bleeding or parasitic infection). Distinct pathophysiological mechanisms impaired erythrocyte production, increased erythrocyte destruction, and iron sequestration or chronic blood loss often overlap, complicating diagnosis and treatment. Recent advances in understanding molecular regulators such as hepcidin and erythroferrone, and therapeutic innovations including hypoxia-inducible-factor (HIF) stabilizers, hepcidin antagonists, gene therapy for haemoglobinopathies, and refined iron-management protocols, promise improved outcomes. This review synthesizes current evidence on mechanisms, diagnostic approaches, and management strategies across major disease categories causing anemia.